(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Globally people have succumbed to viral infections that posed a stupendous threat. Community wearing of facemask helped lowering the incidence of COVID-19. The objective was to determine the public opinion regarding prolonged mask-wearing practice, and to find out the behavioral differences as pertinent compensations for not wearing that may help combat pandemics because of emerging infections. Methodology: This cross-sectional study carried out in the outpatient departments of Military Hospital (MH) Rawalpindi, Pakistan from January to June 2021 after ethical approval. Participants selected by non-probability convenience sampling technique of different residential, economic and educational backgrounds, above 16 years of age, from both genders to give their opinion on a validated questionnaire, “Multidimensional face mask perceptions scale” with eight domains. Results: Among 175 participants, almost 81.7% participants were of the view that when they do not wear mask it is because facemasks get overheated and disrupt the breathing, 60.6% adopted compensation ways by avoiding people and 45.7% considered its wearing a hassle. Female participants felt more uncomfortable by disrupted breathing (p =0.029), male participants reflected about value of independence (p<0.001), and participants from rural area thought a difficult access to get facemasks (p =0.003). Conclusion: The most likely reason for not wearing mask among participants was uncomfortable breathing. The other reasons includes adopting social distancing guidelines as a compensatory measure, finding facemask wearing practice a hassle, interference with freedom and access issues by rural population. Designing and implementing awareness sessions may halt such spread of pandemics because of emerging infections.